PFM.39 Diagnostic accuracy of antenatal magnetic resonance imaging (MRI) to predict birth weight >90th centile or < 10th centile in the third trimester. (9th June 2014) - Malin, G; Anblagan, D; Bugg, G; Gowland, P; Jones, NW; Robinson, R
Abstract : Introduction: Accurate diagnosis of disturbance in fetal size is needed to manage pregnancies and ensure optimal outcome. Conventionally ultrasound is used to estimate fetal weight (EFW) but diagnostic accuracy is poor. Methods: Fetal MRI was performed on a 1.5 Tesla Philips Achieva scanner. Half Fourier Single Shot Turbo Spin-Echo (HASTE) and Balanced Fast Field Echo (bFFE) sequences of the uterine cavity were acquired. Fetal volume was measured by drawing a freehand mask around the fetus in contiguous slices using Analyse 9.0. To convert estimated fetal volume into MR_EFW the formula MR_EFW = 0.12 +1.031 × fetal_volume (1) was used. MR centiles were then calculated using the GROW customised centile calculator. The diagnostic accuracy of MRI in the detection of large (>90 th centile: LGA) and small (<10 th centile: SGA) for gestational age fetuses was calculated by comparison with actual birth-weight centiles. Results: MRI was performed at an average gestational age of 35+0 weeks (SD ± 7 days) in 37 subjects. The average MR_EFW was 2554 (±437) g with a median MR_centile of 42.8. Mean gestational age at delivery was 39+3 weeks (±11 days) with a mean birth-weight of 3349 (±593) g and median birth-weight centile of 34.0. For LGA MRI had sensitivity: 83.3%, specificity: 96.6%, positive predictive value: 83.3% and negative predictive value: 96.6%. Corresponding values for SGA were 57.1%, 100%, 100%, 90.3%, respectively. For birth-weight <5 th centile MRI had a sensitivity and specificity of 100%. Conclusion: In this small study the diagnostic accuracy of MRI_EFW is superior to those quoted for USS_EFW (2, 3). References: Baker PN, Johnson IR, Gowland PA, Hykin J, Harvey PR, Freeman A, et al . Fetal weight estimation by echo-planar magnetic resonance imaging. Lancet . 1994;343(8898):644–5 Chauhan SP, Cole J, Sanderson M, Magann EF, Scardo JA. Suspicion of intrauterine growth restriction: Use of abdominal circumference alone or estimated fetal weight below 10%. J Matern Fetal Neonatal Med . 2006;19(9):557–62 Coomarasamy A, Connock M, Thornton J, Khan KS. Accuracy of ultrasound biometry in the prediction of macrosomia: a systematic quantitative review. BJOG . 2005;112(11):1461–6